2004
DOI: 10.1891/0739-6686.22.1.285
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Complementary and Alternative Medicine Among Racial and Ethnic Minority Populations: Implications for Reducing Health Disparities

Abstract: This chapter provides a review of research literature and describes the use of complementary and alternative medicine (CAM) among racial and ethnic minority populations. The relevance of CAM to health disparities is also discussed. Complementary and alternative medicines are terms used to describe methods of health care beyond the usual Western biomedical model. These treatments are prevalent and increasing in the United States. Many CAM therapies are ancient therapies among certain racial and ethnic minoritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Given an insured population, system inefficiencies, including busy clinics, have been implicated in differences in delay by ethnic/racial groups. 10,36,37 Cultural variations in approaches to cancer detection and follow-up for abnormal findings, including levels of acculturation, or attitudes and beliefs toward cancer causation, preferences in cancer detection, or the perceived effectiveness of treatment may influence the timeliness of services. 38 Although these predictors, too, were unmeasured in this study, patient psychosocial fac- tors, such as fear and anxiety, a sense of fatalism, perceived risk, misunderstanding, body image, the competing demands of caring for others, and social norms, may also delay diagnostic evaluation and treatment.…”
Section: Commentmentioning
confidence: 99%
“…Given an insured population, system inefficiencies, including busy clinics, have been implicated in differences in delay by ethnic/racial groups. 10,36,37 Cultural variations in approaches to cancer detection and follow-up for abnormal findings, including levels of acculturation, or attitudes and beliefs toward cancer causation, preferences in cancer detection, or the perceived effectiveness of treatment may influence the timeliness of services. 38 Although these predictors, too, were unmeasured in this study, patient psychosocial fac- tors, such as fear and anxiety, a sense of fatalism, perceived risk, misunderstanding, body image, the competing demands of caring for others, and social norms, may also delay diagnostic evaluation and treatment.…”
Section: Commentmentioning
confidence: 99%
“…42 Some researchers have suggested that the use of different forms of CAM may help decrease health disparities among ethnic minorities. 52 Increased utilization of chiropractic health care may provide blacks with more diverse health care options, particularly with soft tissue injuries associated with neck and low back pain. Research demonstrates that spinal manipulation can have a positive impact on neck and low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another national probability survey, the use of CAM was equally prevalent among racial/ethnic subgroups (Mackenzie et al, 2003). A recent systematic review of CAM use among minorities concluded that these mixed research findings stem from discrepancies in CAM definitions, CAM practitioners, and diverse methodologies used in the published research (Struthers & Nichols, 2004).…”
Section: Discussionmentioning
confidence: 99%